The Preliminary Study for Budget Monitoring System in Government Agencies - Humairoh, Nayu; Ahmad (PT. Lentera Ilmu Publisher, 2024)
This study explores the critical role of budget monitoring systems in enhancing financial management and accountability within government agencies. Traditional budget monitoring methods, often reliant on outdated software and manual processes, are increasingly inadequate, leading to inefficiencies and errors. The study identifies a pressing need for automated systems that provide real-time data and better integration with existing financial tools. Through a comprehensive needs assessment, literature review, and stakeholder analysis, the research highlights the benefits of adopting modern budget monitoring systems, including improved transparency, efficiency, and decision-making. However, successful implementation requires addressing challenges related to user adoption, training, and the alignment of technology with current infrastructure. The findings underscore the importance of strong leadership and phased implementation to ensure that these systems effectively meet the financial oversight needs of government agencies.